TAPAMA: Media Pembelajaran Majas Perbandingan Berbasis Kearifan Lokal Tanah Papua untuk Siswa Kelas 5 SD : Studi Kelayakan dan Kepraktisan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
. Learning comparative figures of speech in elementary school often faces challenges because the material is abstract, while fifth-grade students are still at the concrete operational stage and require contextual learning support. This study aimed to develop TAPAMA (Tanah Papua and Comparative Figures of Speech), a learning media based on the local wisdom of Papua, and to examine its feasibility and practicality in Indonesian language learning for fifth-grade elementary students. This study employed a Research and Development (R&D) method using the ADDIE model, limited to the implementation stage. Media feasibility was evaluated through expert validation involving media experts, material experts, and language experts, while practicality was assessed through teacher and student response questionnaires. The results showed that TAPAMA learning media was categorized as highly feasible based on expert assessments. Furthermore, the practicality test indicated that TAPAMA was easy to use, attractive, and supportive of classroom learning activities. The media helped students understand comparative figures of speech more concretely through culturally relevant examples derived from the local wisdom of Papua. The findings imply that TAPAMA can serve as an innovative and contextual alternative learning media to support the teaching of comparative figures of speech while fostering students’ appreciation of local culture in elementary schools.